Integrative characterization of the venom of the coral snake Micrurus dumerilii (Elapidae) from Colombia: proteome, toxicity, and cross-neutralization by antivenom - Rey Suárez, Paola (2016)
In Colombia, nearly 2.8% of the 4200 snakebite accidents recorded annually are inflicted by coral snakes (genus Micrurus). Micrurus dumerilii has a broad distribution in this country, especially in densely populated areas. The proteomic profile of its venom was here studied by a bottom-up approach combining RP-HPLC, SDS-PAGE andMALDI-TOF/TOF. Venomproteins were assigned to eleven families, themost abundant being phospholipases A2 (PLA2; 52.0%) and three-finger toxins (3FTx; 28.1%). This compositional profile shows thatM. dumerilii venom belongs to the ‘PLA2-rich’ phenotype, in the recently proposed dichotomy for Micrurus venoms. Enzymatic and toxic venom activities correlated with protein family abundances. Whole venom induced a conspicuous myotoxic, cytotoxic and anticoagulant effect, and was mildly edematogenic and proteolytic, whereas it lacked hemorrhagic activity. Some 3FTxs and PLA2s reproduced the lethal effect of venom. A coral snake antivenom to Micrurus nigrocinctus demonstrated significant cross-recognition of M. dumerilii venomproteins, and accordingly, ability to neutralize its lethal effect. The combined compositional, functional, and immunological data here reported for M. dumerilii venom may contribute to a better understanding of these envenomings, and support the possible use of anti-M. nigrocinctus coral snake antivenom in their treatment. Biological significance: Coral snakes represent a highly diversified group of elapids in the NewWorld,with nearly 70 species within the genus Micrurus. Owing to their scarce yields, the biochemical composition and toxic activities of coral snake venoms have been less well characterized than those of viperid species. In this work, an integrative view of the venom of M. dumerilii, a medically relevant coral snake from Colombia, was obtained by a combined proteomic, functional, and immunological approach. The venom contains proteins fromat least eleven families, with a predominance of phospholipases A2 (PLA2), followed by three-finger toxins (3FTx). According to its compositional profile, M. dumerilii venom can be grouped with those of several Micrurus species from North and CentralAmerica that present a PLA2-predominant phenotype, to date it is themost southerly coral snake species to do so. Other coral snake species that a ‘PLA2-rich’ venom, M. dumerilii venom contains both components that form MitTx, a pain-inducing heterodimeric complex recently characterized from the venom of Micrurus tener, also present in Micrurus mosquitensis and M. nigrocinctus venoms. In addition to a lethal three-finger toxin, PLA2s participate in the toxicity ofM. dumerilii venom, some of them displaying ability to induce cytolysis, muscle necrosis, and lethality to mice. An antivenom to M. nigrocinctus demonstrated significant crossrecognition of M. dumerilii venom proteins, and accordingly, ability to neutralize its lethal effect, being of potential therapeutic usefulness in these envenomings.